Traditional wisdom of post-harvest processing and value addition of arid land food - Meena, M. L.; Singh, Dheeraj; Dudi, Aishwarya (Indian Farming, 2019)
Arid region are unique in terms of agro-climatic features, bio-diversity of flora and fauna and adaptations of plants and animals to harsh and extreme climatic conditions. Though a number of arid foods were exploited commercially and are contributing international agricultural trade, however, there are so many under-utilized arid food crops which are used locally by the people. The nutritional and physiological properties are well established but their commercial exploitation require due attention and incentives. The under-utilized arid food crops have unique physiological specialties which make them as wonder crops of arid world. Value addition is current paradigm shift in agriculture focusing on bio-diversity conservation and economic upliftment of rural community. Desert vegetation has great potential for value addition. Arid food crops of other regions of world need to be introduced as exotic species. Plant physiological attributes suggest adaptability of plants for introduction, selection and cultivation. Arid and semi-arid areas are blessed with large underutilized bio-diversity consisting of trees, shrubs and herbs that are partially utilized as food or food product and medicinal derivates. The commercial production of food products from under-utilized fruit species helped to reduce wastage of fruits and helped in promoting marketing of these items. Sangri, ker, khimpoli, kachri, kumath, phogla, ber, bajara, moth and beria are important traditional value added products of Rajasthan arid ecosystem which are transported and happily eaten throughout the country and some of these are exported.